FAKTOR-FAKTOR YANG MEMPENGARUHI NON PERFORMING FINANCING BANK PEMBIAYAAN RAKYAT SYARIAH DI INDONESIA - Mastura; Mastura, Mastura; Maulana, zefri; Midesia, Shelly; Nurjannah, Nurjannah (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
This study aims to analyze the influence of financing to deposit ratio, capital adequacy ratio, and total financing on non-performing financing of Sharia People's Financing Banks (BPRS) in Indonesia. The data used in this study is secondary data obtained from the official website of the Financial Services Authority published in the 2014-2022 period. The research method used is a quantitative method with the data analysis technique used is multiple linear regression. The results of this study show that the ratio of financing to deposits, capital adequacy ratio, and total financing partially affect BPRS non-performing financing in Indonesia. The results of the study also show that the ratio of financing to deposits, capital adequacy ratio, and total financing simultaneously affect BPRS's non-performing financing in Indonesia. The results of the study also show that the variables Financing to Deposit Ratio, Capital Adequacy Ratio, and Total Financing are able to explain the BPRS Non-Performing Financing variable in Indonesia by 33.3%. Recommendations for regulators to provide incentive policies or technical assistance for BPRS that have high NPF levels in order to improve their financial performance.